Effect of Ultrasonic Vibration on Microstructure Hot Glass Embossing Process - Nguyen, Lan Phuong; Wu, Ming-Hui; Hung, Chinghua (Old Journal, 2017)
Hot glass embossing is a novel technology to manufacture microstructures for Field Emission Displays. By this technology, microstructures on the mold could be embossed on the glass surface with high quality and lower cost. Although effect of ultrasonic vibration on micro-formability of glass material has been studied in some previous research, no consideration has been performed with pyramid array which possesses small tip angle. The aim of this work is to utilize ultrasonic vibration with frequency of 35 kHz and amplitude of 3 µm to improve the filling ability of K-PSK100 glass into pyramid shaped-microcavities. This study also proposed to use an impression mold to enhance the filling ability for the glass. Experimental data showed that micro-formability of glass material could be improved 17% under effect of ultrasonic vibration and more 3% as using the impression mold.